PERAN PERMAINAN TRADISIONAL TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK - Umu Da'watul Choiro (Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
This study aims to determine the role of traditional chutilan games in improving the fine motor skills of children aged three to four years. Chutilan is a traditional game played using sticks. The research approach used is qualitative with a descriptive design. The research was conducted at KB Al Ilmu, Maindu, Montong, Tuban with the research subjects being children in the play group. Data was collected by conducting observations, interviews and documentation. Data analysis was carried out by explaining the data that had been collected. Data analysis using triagulation technique. This study found that children playing traditional chutilan games on the developmental aspects of children's abilities, especially fine motor skills, could observe their fine motor development skills through chutilan games, children were able to move sticks from one hand to another.